"Mr Right Now": Temporality of relationship formation on gay mobile dating apps. (January 2018) - Yeo, Tien Ee Dominic; Fung, Tsz Hin
Mobile dating apps with geolocation function have gained popularity for fostering social, romantic, and sexual connections between nearby strangers. Through in-depth interviews and focus-group discussions with 74 users of gay mobile dating apps (Grindr and Jack'd) in Hong Kong, this study illustrates how the sociological concept of time can shed light on users' experience of relationship formation through these apps. Specifically, the accelerated tempo of interactions facilitated by perpetual connectivity, mutual proximity awareness, and instant messaging was seen to entail instantaneous and ephemeral relationships. The interface design, which foregrounds profile photos and backgrounds textual self-descriptions, was perceived to structure the sequence of browsing and screening in favor of physical appearance and users seeking casual hook-ups. The findings suggest that the temporality of browsing and exchange on apps is incongruous with the temporal norms prescribing formation of friendship and long-term romance. Such incongruity affects the perceived quality and satisfaction of app use, frustrating users who seek more durable relationships.